KEPATUHAN HUKUM DALAM BERNIAGA MENURUT UMAR BIN KHATTAB (Studi Kasus Akuisisi TikTok Shop dan Tokopedia) - Puspa Indriani Harahap; Imam Yazid (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
Trade is a dynamic economic activity, governed by laws that continually evolve over time. In Indonesia, the implementation of Minister of Trade Regulation No. 31 of 2023 on Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Electronic Commerce has significantly impacted the landscape, notably resulting in the closure of TikTok Shop in 2023. This research seeks to explore the legal foundation underlying the prohibition of social commerce platforms from conducting trade transactions, as stipulated in MOT 31/2023, and to examine the concept of legal compliance in trade through the lens of Umar bin Khattab’s legal principles. The study employs a normative-juridical approach, framed by the theory of legal compliance. The findings reveal that the restriction on social commerce platforms from facilitating payment transactions on their own platforms is intended to mitigate conflicts of interest in electronic transactions. Furthermore, adherence to the legal principles of trade, as outlined by Umar bin Khattab, is regarded as fundamentally crucial and must be upheld within the framework of trade ethics